Impact of Dual Antibiotic Prophylaxis on 90-Day Surgical Site Infection Rates Following Posterior Spinal Fusion for Juvenile Scoliosis: A Single-Center Study of 296 Cases - Paolo Brigato; Davide Palombi; Leonardo Oggiano; Sergio De Salvatore; Alessandro Rogani; Sergio Sessa; Pier Francesco Costici (Medicina)
Background and Objectives: Surgical site infections (SSIs) significantly impact pediatric spinal deformity surgery. Considering the increased risk of Gram-negative infections in neuromuscular scoliosis (NMS), broader antibiotic coverage could be advantageous. Some studies suggest extending this approach to all scoliosis etiologies to reduce SSI rates. This study evaluates whether a dual antibiotic prophylaxis with cephalosporin and aminoglycoside reduces SSI incidence within 90 days postsurgery in adolescent idiopathic scoliosis (AIS), NMS, and syndromic scoliosis (SS) patients. Materials and Methods: This study included pediatric patients with AIS, NMS, or SS curves, treated with posterior spinal fusion between January 2019 and December 2022, with a minimum two-year follow-up. The primary outcome was early SSI incidence and its correlation with dual antibiotic prophylaxis in pediatric scoliosis surgery. Secondary outcomes included operative data, blood loss, hemoglobin levels, hospital stay, complications, pelvic fixation, and radiographic correction and how these factors could be identified as potential risk factors for SSIs. Descriptive and inferential statistics were used to analyze antibiotic regimen, SSI risk, and perioperative variables using chi-square, Mann–Whitney U, ANOVA, and Cox regression. Significance was set at p < 0.05. Results: The study included 296 patients: 222 with AIS, 46 with NMS, and 28 with SS. Ninety days postsurgery, SSI rates were 1.2% in AIS (0.8% deep, 0.4% superficial), 6.5% in NMS (all superficial), and 3.5% in SS (all superficial). Deep SSIs in AIS were associated with methicillin-resistant Staphylococcus aureus (MRSA). None of the cases required implant removal. Univariate Cox regression did not reveal any statistically significant predictors for SSIs. However, older age at surgery showed a protective trend, while higher preoperative ASA scores seemed to be a negative prognostic factor (respectively p = 0.051 and p = 0.08). Conclusions: Dual antibiotic prophylaxis with cefazolin and amikacin was associated with a lower SSI rate after posterior spinal fusion for scoliosis, with no adverse events. Further studies are needed to refine dosage, timing, and duration.